The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmars.2022.837877
|View full text |Cite
|
Sign up to set email alerts
|

High Coral Recruitment Despite Coralline Algal Loss Under Extreme Environmental Conditions

Abstract: The crucial role of crustose coralline algae (CCA) in inducing hard coral larval settlement and ensuring the replenishment of coral reefs is widely accepted, and so are the negative effects of anthropogenic CO2 emissions on both CCA abundance and coral development. However, diversified and well-developed coral reef communities have been recently discovered in natural conditions where CCA and corals would not be expected to thrive. Back-reef pools, volcanic CO2 vents, mangrove estuaries, and semi-enclosed lagoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
(163 reference statements)
1
5
0
Order By: Relevance
“…Following the bleaching event, the reef has experienced a change from CCA domination to turf algae which increased by 50% post-bleaching. This nding aligns with other studies in various locations such as Hawaii (Foo et al 2022) and New Caledonia (Tanvet et al 2022) all of which is attributed to SST warming (Cornwall et al 2019). Therefore, the high presence of CCA is evidence that this reef is in recovery but has been affected by this warming event which is impacting the recovery process (Teichert et al 2020;Roth et al 2018).…”
Section: Carbonate Productionsupporting
confidence: 90%
“…Following the bleaching event, the reef has experienced a change from CCA domination to turf algae which increased by 50% post-bleaching. This nding aligns with other studies in various locations such as Hawaii (Foo et al 2022) and New Caledonia (Tanvet et al 2022) all of which is attributed to SST warming (Cornwall et al 2019). Therefore, the high presence of CCA is evidence that this reef is in recovery but has been affected by this warming event which is impacting the recovery process (Teichert et al 2020;Roth et al 2018).…”
Section: Carbonate Productionsupporting
confidence: 90%
“… 92 Whilst the light intensity used in ‘shallow’ aquaria may be considered relatively low for 5 m depth at the planulae collection site (Eilat, Gulf of Aqaba), the intensity (together with the well-matched spectrum) may be considered as a simulation of a partially shaded ‘shallow’ reef which coral planulae under high light conditions typically seek. 93 , 94 , 95 , 96 , 97 Variable sample sizes were an unavoidable result of differences in the total number of larvae collected from each depth, resulting in an unbalanced design. Triplicate aquaria for were used for each light condition with planulae distributed as evenly as possible between aquaria.…”
Section: Methodsmentioning
confidence: 99%
“…As such, understanding the dynamics of macroalgal responses to heat stress and their interac�ons with other benthic groups can help us understand not only grouplevel responses, but also make reef-scale mul�-species predic�ons. Finally, while some studies have found that coralline algae is crucial setlement media for coral larvae, and coralline algae can be killed by heat stress (Webster et al 2011;Tebben et al 2015;Tanvet et al 2022), we have litle informa�on on the dynamics of coralline algae through coral bleaching events. Understanding how sponges and algae respond to heat stress is crucial to understanding the full dynamics of heat stress on reefs and their role in inhibi�on or facilita�on of coral reef recovery.…”
mentioning
confidence: 93%
“…Addi�onally, they provide food and habitat for many mobile species including specialist to non-stony coral habitat builders (Pratchet 2007;Epstein and Kingsford 2019). The majority of studies on reef impacts focus on how stony corals have been affected and o�en include other groups only when they are nega�vely impac�ng stony coral health, such as compe��on with or overgrown of corals by algae or sponges (Coll et al 1987;Lapointe et al 2007;Clements and Hay 2023), or recruitment of stony coral larvae to coralline algae (Webster et al 2011;Tebben et al 2015;Tanvet et al 2022). While it is important to understand how stony corals respond to stressors as they build the founda�on of reef structures, it is also important to understand how all habitat building species may be affected in order to disentangle reef-scale dynamics.…”
mentioning
confidence: 99%